Does MBA’s paradigm transformation follow business education’s philosophy? a comparison of academic and job-performance and SES among five types of MBAian - Alam, Gazi Mahabubul; Giacosa, Elisa; Mazzoleni, Alberto (Elsevier, 2022)
Traditionally, students are enrolled in a specialised postgraduate program based on their undergraduate record. The MBA is a unique program where students who have done courses such as business, engineering, medicine, science, arts, etc., can enrol. Based on different requirements for enrolling in the MBA, various types of MBAian are produced. Research for this paper, which is the first of its kind, compares both academic and job-performance as well as SES (socioeconomic status) of five types of MBAian. The aim here is to contribute to the literature on “human capital theory” by balancing “dynamic capabilities”. Adopting a “descriptive analysis” to both secondary and primary data, this study asserts that the MBAians who originally were from the science stream at secondary level did better in the MBA compared to graduates who learnt business at secondary school. Of five job competencies, the MBAian from science stream performed well in three while their counterparts who studied business education in the first degree did well in two. The MBAian from science stream come from a privileged socioeconomic background and their academic results from the secondary provision are better compared to the other four groups. Graduates with relevant prior business education backgrounds did not perform well in MBA programs. A good SES and earlier academic results helped the MBAian to succeed. This indicates that business education has no effect in mitigating the role of SES. A policy framework is presented to ensure a symbiotic interaction between different types of business education (secondary to postgraduate).